Supersaturated-Silica Lipid Hybrids Improve in Vitro Solubilization of Abiraterone Acetate - Schultz, Hayley B.; Joyce, Paul; Thomas, Nicky; Prestidge, Clive A. (Pharmaceutical research, 2020)
Purpose Abiraterone acetate (AbA) is a poorly water-soluble drug with an oral bioavailability of <10% and a significant pharmaceutical food effect. We aimed to develop a more efficient oral solid-state lipid-based formulation for AbA using a supersaturated silica-lipid hybrid (super-SLH) approach to achieve high drug loading, improve in vitro solubilization and mitigate the food effect, while gaining a mechanistic insight into how super-SLH are digested and release drug. Methods The influence of super-SLH saturation level and lipid type on the physicochemical properties and in vitro solubilization during lipolysis of the formulations was investigated and compared to the commercial product, Zytiga. Results Super-SLH achieved significantly greater levels of AbA solubilization compared to Zytiga. Solubilization was influenced by the AbA saturation level, which determined the solid state of AbA and the relative amount of lipid, and the lipid utilized, which determined its degree of digestion and the affinity of the lipid and digestion products to the silica. A fine balance existed between achieving high drug loads using supersaturation and improving performance using the lipid-based formulation approach. The non-supersaturated SLH prepared with Capmul PG8 mitigated the 3-fold in vitro food effect. Conclusion SLH and super-SLH improve in vitro solubilization of AbA, remove the food effect and demonstrate potential to improve oral bioavailability in vivo. Graphical Abstract Abiraterone acetate was formulated as silica-lipid hybrids and demonstrated enhanced in vitro solubilization in comparison to pure abiraterone acetate and commercial product, Zytiga